2023
DOI: 10.1111/ped.15449
|View full text |Cite
|
Sign up to set email alerts
|

Psychological characteristics of juvenile fibromyalgia syndrome

Abstract: BackgroundThe aim of the study was to compare psychological characteristics of adolescent patients with juvenile fibromyalgia syndrome (JFM) with individuals suffering from chronic pain (CP) due to headache or joint pain in the lower limbs unrelated to oncological, inflammatory or autoimmune diseases.MethodsThe study was conducted on 37 patients aged 13–18 years old, monitored at the Pain Therapy Outpatient Clinic of the “Bambino Gesù” Pediatric Hospital in Rome. A total of 21 patients were suffering from CP (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…This is important because the estimated prevalence of chronic widespread pain (CWP) among children and adolescents in primary care is as high as 3.19% ( 9), but there are currently no diagnostic criteria for JFM and children are obliged to undergo sub-specialty referrals and extensive imaging and testing (10). Dell'Erba et al (11) have compared the psychological characteristics of JFM patients with those of subjects affected by chronic headache or joint pain, and found that both groups had similar characteristics in terms of depression, anxiety, somatisation, alexithymia, school absenteeism, medication use, and reported pain levels. However, the JFM group was characterised by a higher proportion of females, a higher incidence of sleep disturbances, and better cognitive abilities despite some attention and memory deficiencies.…”
Section: Reviewmentioning
confidence: 99%
“…This is important because the estimated prevalence of chronic widespread pain (CWP) among children and adolescents in primary care is as high as 3.19% ( 9), but there are currently no diagnostic criteria for JFM and children are obliged to undergo sub-specialty referrals and extensive imaging and testing (10). Dell'Erba et al (11) have compared the psychological characteristics of JFM patients with those of subjects affected by chronic headache or joint pain, and found that both groups had similar characteristics in terms of depression, anxiety, somatisation, alexithymia, school absenteeism, medication use, and reported pain levels. However, the JFM group was characterised by a higher proportion of females, a higher incidence of sleep disturbances, and better cognitive abilities despite some attention and memory deficiencies.…”
Section: Reviewmentioning
confidence: 99%